2015
DOI: 10.3109/03630269.2015.1037890
|View full text |Cite
|
Sign up to set email alerts
|

α-Thalassemia: Genotypic Profile Associated with Ethnicity and Hematological Differentiation of Iron Deficiency Anemia in the Region of Uberaba, Minas Gerais, Brazil

Abstract: α-Thalassemia (α-thal) is a hereditary hemoglobinopathy characterized by microcytic anemia due to impaired production of α chains of human globin. Brazilian studies show that the most common genotype is an -α(3.7) deletion with the loss of one or two α genes. As the production of α chains is not as accentuated in these cases, the correct diagnosis can only be achieved through molecular analysis that is not usually routinely performed by laboratories. We investigated the occurrence of α-thal babies born between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 34 publications
0
6
1
1
Order By: Relevance
“…e α-thalassemia alleles frequency found from the random blood donors' samples is similar to that estimated in other studies from Brazilian population (average among 2.5-8%). Our study showed lower α-thalassemia frequency when compared to 14.89% reported in the Uberaba Regional Blood Center's (Hemominas Foundation, Uberaba, Brazil) work, with all cases being heterozygous for the -α 3.7 deletion [21][22][23].…”
Section: Resultscontrasting
confidence: 56%
“…e α-thalassemia alleles frequency found from the random blood donors' samples is similar to that estimated in other studies from Brazilian population (average among 2.5-8%). Our study showed lower α-thalassemia frequency when compared to 14.89% reported in the Uberaba Regional Blood Center's (Hemominas Foundation, Uberaba, Brazil) work, with all cases being heterozygous for the -α 3.7 deletion [21][22][23].…”
Section: Resultscontrasting
confidence: 56%
“…Quando um gene é afetado, acarreta em um portador silencioso, e se dois genes são mutados, resulta no traço α-talassemico. Já a Doença da Hemoglobina H ocorre quando três genes são impactados e a síndrome da Hidropisia Fetal quando os quatros genes alfa estão comprometidos 13,14,15 .…”
Section: Resultados E Discussão Talassemia Alfaunclassified
“…Anemia, and particularly IDA, is one of the factors that leads to deferral of blood donor candidates with multiple blood donations being recognized as a cause of ID and anemia [6,9,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that IDA is the main cause of ineligibility in blood donors, especially among women, as observed in this study (Women: 38.2% vs. Men: 1.9%). This result is explained by blood loss during menstrual cycles or gestations [1,5,9,15,16]. In addition to the main related causes, studies have also shown that the frequency of donations may be a potential risk factor for ID [10,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation